2020
DOI: 10.1021/jacs.9b11606
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Supported Organolanthanum Catalysts for C–O Bond Cleavage in Epoxides

Abstract: Single-site organolanthanum complexes supported on mesoporous silica nanoparticles, La{C(SiHMe2)3}n@MSNs, catalyze the ring-opening hydroboration reaction of aliphatic and styrenic epoxides with pinacolborane (HBpin). The surface-bound complexes, synthesized by reaction of the homoleptic tris(alkyl)lanthanum La{C(SiHMe2)3}3 and SBA-type MSN treated at 700 °C (MSN700), are mostly monopodal ≡SiO-La{C(SiHMe2)3}2 and contain an average of one bridging La↼H-Si per alkyl ligand. This structure was established throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 76 publications
(222 reference statements)
1
19
0
Order By: Relevance
“…Furthermore, hydrolysis of the resulting precipitate with CD 3 OD afforded BpinOD, a reaction outcome from HBpin with CD 3 OD (Figure S5 in the Supporting Information (SI)) . These observations showed that the composition of the resulting precipitate was a lanthanum hydride material like [La-H@SBA-15]·HBpin. ,, Remarkably, the resulting white precipitate, when isolated, exhibited activity toward amide reduction comparable to the active species generated in situ. In addition, the stoichiometric reaction between La­(CH 2 C 6 H 4 NMe 2 - o ) 3 @SBA-15 and C 6 H 4 CONH 2 in 1:5 molar ratio afforded CH 3 C 6 H 4 NMe 2 - o and a precipitate (Scheme b).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, hydrolysis of the resulting precipitate with CD 3 OD afforded BpinOD, a reaction outcome from HBpin with CD 3 OD (Figure S5 in the Supporting Information (SI)) . These observations showed that the composition of the resulting precipitate was a lanthanum hydride material like [La-H@SBA-15]·HBpin. ,, Remarkably, the resulting white precipitate, when isolated, exhibited activity toward amide reduction comparable to the active species generated in situ. In addition, the stoichiometric reaction between La­(CH 2 C 6 H 4 NMe 2 - o ) 3 @SBA-15 and C 6 H 4 CONH 2 in 1:5 molar ratio afforded CH 3 C 6 H 4 NMe 2 - o and a precipitate (Scheme b).…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, to overcome the drawbacks of the homogeneous catalysts in catalyst contamination in reaction outcomes and poor recyclability, increasing interest has been directed toward developing supported catalysts in surface organometallic chemistry (SOMC). Such catalysts not only show the high activity of homogeneous catalysts but also display the ease of separation and recyclability of heterogeneous catalysts, allowing for better control of the whole synthetic process. Consequently, the immobilized heterogeneous rare-earth metal complexes have received much interest in SOMC and have demonstrated interesting performance in organic synthesis and polymerization. Very recently, we developed the well-defined silica-grafted rare-earth metal benzyl materials Ln­(CH 2 C 6 H 4 NMe 2 - o ) 3 @SBA-15 (Scheme ) and found that they exhibited extremely high selectivity and good recyclable property in the transformation of primary arylsilanes into secondary arylsilanes through redistribution. , This interesting finding prompted us to explore their catalytic potential in other organic transformations. Inspired by the elegant work reported by the Marks group and the Chen group using rare-earth metal complexes Ln­[N­(SiMe 3 ) 2 ] 3 as catalysts in amide reduction, , it was envisaged that Ln­(CH 2 C 6 H 4 NMe 2 - o ) 3 @SBA-15 (Ln–C σ-bonded species) possesses promising catalytic performance in amide reduction owing to its bond disruption enthalpy comparable to the amide analogues (Ln–N σ-bonded complexes) .…”
Section: Introductionmentioning
confidence: 99%
“…A critical consideration in the catalytic H 2 production is the regeneration of the catalyst from the borate and aluminate byproducts, which is required to close the hydrogen cycle. This is very challenging due to the inefficiency in the process of breaking an O–B­(Al) bond in the byproduct to generate a B–H bond. Utilizing the local mode analysis to inspect the intrinsic bond strength of O–B­(Al) bond(s) in the byproduct, we were able to shed some new light on the regenerability of the catalyst, which is a complex process and a comprehensive analysis is required, however, to further understand its proper mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…A surface is a nanoscale film placed on a solid or liquid support. In the former case, whether it is about proteins on nanoparticles, innovative materials, heterogeneous catalysis, , or today’s practical application, it is about specific effects induced by the surface of a rigid host on a mobile and/or flexible guest for predetermined purposes. Silica is probably the most common host for inorganic, organic, and biomolecules .…”
Section: Introductionmentioning
confidence: 99%